STUDI PENGARUH LAMA WAKTU PENGADUKAN TERHADAP KUAT TEKAN BETON - Upin, La Ode; Puspitasari, Ira (Jurnal Mahasiswa Terapan; Vol 1 No 3 (2025): Jurnal Mahasiswa Terapan, 2025)
This research was conducted by testing the effect of varying concrete mixing durations, divided into three time groups: 10 minutes, 20 minutes, and 30 minutes. Compressive strength testing was conducted after the concrete had undergone a 28-day curing process. The test specimens used were cylindrical specimens measuring 15 cm x 30 cm. Three samples were tested for each mixing time variation, resulting in a total of nine test specimens. Based on the test results, concrete mixed for 10 minutes demonstrated a maximum compressive strength of 13.01 MPa. The 20-minute mixing time achieved the highest compressive strength of 15.48 MPa, and the same value was also achieved for concrete mixed for 30 minutes. Of the three durations, the 30-minute mixing time produced the highest average compressive strength, at 14.02 MPa. For the unit weight test, the 30-minute mixing time achieved the highest value at 2.30 g/cm³. Meanwhile, stirring for 10 and 20 minutes produced the same maximum bulk density, namely 2.29 gr/cm³.